The impact of monetary policy on monetary stability in Iraq for the period (2004-2018) - Muhammed Noori Farhan; Ali Talib Hussein; Omar Hameed Majeed (Genius Journals, 2022)
Monetary policy is an important part of the economic policy to influence the monetary aspect of stabilization, for this reason the research will seek to clarify the extent of the impact of monetary policy in achieving monetary stability in Iraq during the chosen research period, because the Iraqi economy suffers from monetary instability due to political and security turmoil, Therefore, an effective and effective monetary policy is required in terms of reducing inflationary pressures to reach the required monetary stability, in order to create the appropriate monetary environment for the work of the economic and productive sectors. Thus, the research adopted a basic hypothesis that monetary policy in Iraq has a clear impact on achieving monetary stability.
Keywords: Monetary; Policy; Monetary Stability; Inflation